Patched-Related Is Required for Proper Development of Embryonic Drosophila Nervous System - Bolatto, Carmen; Nieves, Sofía; Reyes, Agustina; Olivera-Bravo, Silvia; Cambiazo, Verónica (Frontiers in Neuroscience, 2022)
Patched-related (Ptr), classified primarily as a neuroectodermal gene, encodes a protein with predicted topology and domain organization closely related to those of Patched (Ptc), the canonical receptor of the Hedgehog (Hh) pathway. To investigate the physiological function of Ptr in the developing nervous system, Ptr null mutant embryos were immunolabeled and imaged under confocal microscopy. These embryos displayed severe alterations in the morphology of the primary axonal tracts, reduced number and altered distribution of the Repo-positive glia as well as peripheral nervous system defects. Most of these alterations were recapitulated by downregulating Ptr expression specifically in embryonic nerve cells. Because similar nervous system phenotypes have been observed in hh and ptc mutant embryos, we evaluated the Ptr participation in the Hh pathway by performing cell-based reporter assays. Clone-8 cells were transfected with Ptr-specific dsRNA or a Ptr DNA construct and assayed for changes in Hh-mediated induction of a luciferase reporter. The results obtained suggest that Ptr could act as a negative regulator of Hh signaling. Furthermore, co-immunoprecipitation assays from cell culture extracts premixed with conditioned medium revealed a direct interaction between Ptr and Hh. Moreover, in vivo Ptr overexpression in the domain of the imaginal wing disc where Engrailed and Ptc coexist produced wing phenotypes at the A/P border. Thus, these results strongly suggest that Ptr plays a crucial role in nervous system development and appears to be a negative regulator of the Hh pathway.